2016
DOI: 10.1002/adv.21662
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cenosphere on the Erosion Wear Response of Woven Hybrid Jute–Glass Epoxy Composites

Abstract: In the present case, the solid particle erosion characteristics of the cenosphere‐filled glass–jute (GJJG) hybrid epoxy composites have been studied experimentally. Jute with (45°−45°) and glass with (0−90°) fabric orientation have been used to fabricate the composites. Different doses of cenosphere particles (5, 10, 15, and 20 wt%) were also added to the matrix material. A steady‐state erosion rate of these composites has been studied with various impingement angles (30°, 45°, 60°, and 90°) with different imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…It was revealed that the addition of cenophere increases the erosion resistance, but an increment in the weight percentage of cenosphere particles beyond a certain threshold leads to a reduction in impact velocity. [421] Abhishek F I G U R E 3 2 Schematic representation of the effects of alkali and high intensity ultrasound treatments on the sisal fibers [416] et al fabricated hybrid epoxy composites containing carbon fiber, Phoenix pusilla plant dry leaves and a nanofiller made from fish bones. The results validated that adding the bio-nanofillers to the hybrid polymer composites permits an enhancement in the tensile strength, flexural strength, and hardness of the composites.…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…It was revealed that the addition of cenophere increases the erosion resistance, but an increment in the weight percentage of cenosphere particles beyond a certain threshold leads to a reduction in impact velocity. [421] Abhishek F I G U R E 3 2 Schematic representation of the effects of alkali and high intensity ultrasound treatments on the sisal fibers [416] et al fabricated hybrid epoxy composites containing carbon fiber, Phoenix pusilla plant dry leaves and a nanofiller made from fish bones. The results validated that adding the bio-nanofillers to the hybrid polymer composites permits an enhancement in the tensile strength, flexural strength, and hardness of the composites.…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…on the erosion rate of the polymer composite. [2][3][4][5] In addition to this, Dalbehera and Acharya 3 along with Antil et al 6,7 studied the additional effect of particulate fillers along with fibers on the erosion behavior of epoxy based composites. The authors are of the view that the addition of particulate filler like SiCp and cenosphere improves the wear resistance of unreinforced fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, AESO modified epoxy resin reinforced with four-ply jute woven fabrics and are produced by the vacuum infusion method. When literature is examined, it is seen that mostly four, six, eight and ten plied fabric reinforced composite plates were produced [35][36][37][38][39][40][41][42][43][44][45]. Since the main aim of this study is to investigate the effect of bio-resin ratio on the properties of composite material, the minimum number of fabric layers (4) is chosen.…”
Section: Introductionmentioning
confidence: 99%